Exploring the Impact of Social Innovation and Managerial Ability on the Financial Performance of Social Enterprises: The Mediating Role of Social Performance - Gusnardi Gusnardi; Yesi Mutia Basri; Hariadi Yasni; Novita Indrawati; Atiza Arrahmi (Universitas Pendidikan Ganesha, 2024)
Indonesia's efforts to achieve Social Development Goals (SDGs) targets through social enterprises play an essential role in addressing economic and environmental issues. However, these enterprises face numerous challenges and constraints. This study aims to investigate how social innovation and managerial ability affect the financial performance of social enterprises. Additionally, this research examines the role of social performance as a mediator. The population in this research consists of social enterprises in Riau Province, specifically cooperatives, waste banks, and medical clinics. A stratified random sampling technique was used to select the sample, with respondents being leaders and heads of business units in each social enterprise. A total of 226 respondents participated through the distribution of questionnaires. Data analysis using WarpPLS 7.0 reveals that social innovation and managerial ability positively influence the financial success of social enterprises. Furthermore, the mediating role of social performance significantly strengthens the connection between social innovation, managerial ability, and financial performance. These findings highlight the importance of enhancing social innovation and managerial skills to improve both social and financial outcomes for social enterprises. This research provides valuable insights for policymakers, practitioners, and social entrepreneurs aiming to optimize the impact of social enterprises in achieving sustainable development goals.